Female Genital Mutilation/Cutting: The Secret World of Women as Seen by Men - Adriana Kaplan; Babucarr Cham; Lamin A. Njie; Ana Seixas; Sandra Blanco; Mireia Utzet (Obstetrics and Gynecology International)
Efforts aimed at the abandonment of Female Genital Mutilation/Cutting (FGM/C) in the communities where it is deeply rooted have extensively considered and addressed women’s perceptions on the issue, leaving those of men barely acknowledged. Although the practice is generally confined to the secret world of women, it does not mean that men cannot be influential. Indeed, men can play an important role in prevention. In order to address this gap, and having as background an extensive ethnographic field work, a transversal descriptive study was designed to explore Gambian men’s knowledge and attitudes towards FGM/C, as well as related practices in their family/household. Results show ethnic identity, more than religion, as the decisive shaping factor on how men conceive and value FGM/C. The greater support towards the practice is found among traditionally practicing groups. A substantial proportion of men intend to have it performed on their daughters, although reporting a low involvement in the decision making process, with very few taking alone the final decision. Only a minority is aware of FGM/C health consequences, but those who understand its negative impact on the health and well-being of girls and women are quite willing to play a role in its prevention.